Designs of Maggot Rotary Dryer to Support Alternative Feed Production - Kamaludin, Muhamad; Agus Haris Abadi; Masri Bin Ardin; Rian Dwi Aji Saputro; Nurizzi Rifqi Ferdian; Dadang Hafid; Asep S. Setyadin (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
The growth of maggot cultivation as an alternative feed source is increasing in response to the demand for sustainable organic waste management solutions. However, the drying process remains a major challenge, especially for small and medium-scale operations. This study aims to design and develop a 20-kg capacity rotary maggot dryer that is efficient, energy-saving, and suitable for community-scale production. The design method includes user needs analysis, material selection, CAD-based design simulation, and testing tool performance. The results indicated that the dryer can reduce maggot moisture content within an average drying time of 3 hours at 60–70°C with relatively low energy consumption. This innovation is expected to improve maggot production efficiency and promote appropriate technology for sustainable alternative feed development at the community level.